Social Informatics Turns under Geo-Political Economic Dynamics: The Battle for Technological Hegemony and Soft Power in the 5G Era - Takahiro Kawamata (International Telecommunications Society (ITS), 2022)
Currently, technological competition over 5G is turning into a struggle not only for economic hegemony but also for political hegemony related to national security, while guiding, dividing, monitoring, and controlling by "information" that appears in the network society. The aspect of is deepening. A glimpse of that step from the path dependence of the technology trajectory leads to the 2nd & 3rd generation of digital mobile technology. Having the establishment of dominant positions in the second and third generations' mobile phone market with the European standard GSM and the global standard W-CDMA, NOKIA takes Apple lead in conversion to smartphones in the transition to the fourth generation Forgiveness, in line with Google's Android OS equipped Samsung's catch-up, it was decided to lose its position in the mobile terminal market ("NOKIA shock"). The transformation to the fourth generation is different from the market competition that takes advantage of the "scale economy" backed by the dominant design of handsets seen in previous generation changes, and the development of the app market. The terminal itself has become a mere input/output device of the platform application in the competition in the "economy of scope" with the multi-functions of the service. Here, Samsung, which integrates the element technology of the terminal device, becomes a competitive factor as to how the functionality of the application can be exhibited, and Apple, Inc., which holds the app approving right from the device design and has controllability in fragmentation of the global market progressed by utilizing EMS (Electronics Manufacturing Service). On the other hand, in the Asian market, in which the development of the mobile communication backbone has progressed rapidly, emerging mobile handset manufacturers are emerging in China, which has a strong domestic market. The foremost tip was Huawei, which was trying to occupy the global market for the fifth generation. However, it came here and the war between the United States and China was cut off. It has not only been an imbalance issue of trade (balance of payments) but has spread to an international issue that extends to the issue of intellectual property rights related to national security and technology development ("Huawei Exclusion"). (...) This paper examines the industrial technology segment strategies of companies in the social acceptance of technology within a global geopolitical and economic framework, with a view to today's 5G developments, based on the technological trajectory to date.
Keywords: 330